Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja (SMK3) Pada Proyek Pembangunan Jalan - Shelly Puspita Ayu Wardhani; Kartono Wibowo; Soedarsono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to evaluate the implementation and success rate of the Occupational Safety and Health Management System “SMK3” in construction projects, referring to Government Regulation (PP) Number 50 of 2012. The method used is descriptive qualitative. The results of the analysis show that the level of implementation of “SMK3” reached 90.96% with the predicate “Satisfactory”. This indicates that the contractor has carried out the duties and functions of “SMK3” well and in accordance with regulations. The implementation of “SMK3” in this project includes several regulations, such as the use of Personal Protective Equipment (PPE) according to the type of work, calls to obey signs, maintain cleanliness, and report emergencies. In addition, this regulation also regulates hazard identification and risk assessment. Overall, it can be concluded that the implementation of “SMK3” in this project is in accordance with PP No. 50 of 2012. The satisfactory implementation of “SMK3” is able to create a safe and productive work environment. Keywords: Identification, Implementation of “SMK3”, PP No. 50 of 2012, Success Rate of SMK3.